The avoidance of pre-bankruptcy transactions: An economic and comparative approach - GURREA-MARTINEZ, Aurelio (Institutional Knowledge at Singapore Management University, 2018)
Most insolvency jurisdictions provide several mechanisms to reverse transactions entered into by a debtor prior to the commencement of the bankruptcy procedure. These mechanisms, generally known as claw-back actions or avoidance provisions, may fulfil several economic goals. First, they act as an ex post alignment of incentives between factually insolvent debtors and their creditors, since the latter become the residual claimants of an insolvent firm but they do not have any control over the debtor´s assets while the company is not yet subject to a bankruptcy procedure. Thus, avoidance powers may prevent or, at least, reverse opportunistic behaviors faced by factually insolvent debtors prior to the commencement of the bankruptcy procedure. Second, these devices may also prevent the creditors’ race to collect when insolvency threatens. Therefore, the existence of avoidance actions may reduce, at an early stage, the ‘common pool’ problem that bankruptcy law seeks to solve. Third, avoidance powers also protect the interests of both the debtor and its creditors when the former is facing financial trouble and some market participants want to take advantages of this situation. Finally, the avoidance of pre-bankruptcy transactions can also be helpful for the early detection of financially distressed debtors, so it may encourage managers to take corrective actions in a timely manner. As a result of these goals, the existence of avoidance powers can create several benefits. However, the use –and even existence– of avoidance actions is not costless. On the one hand, the use of these actions may generate litigation costs. On the other hand, the existence of these mechanisms may harm legal certainty, especially in countries in which it is relatively easy to avoid a transaction, usually because bad faith is not required, the look-back period may be too long, or no financial conditions are required to avoid a transaction. Therefore, insolvency legislators should carefully deal with these costs and benefits in order to make sure that the existence of avoidance powers does not do more harm than good. On the basis of this exercise, this paper analyzes, from a comparative and functional approach, the optimal way to design claw-back actions across jurisdictions.